If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(w + -8) = -33 Reorder the terms: 3(-8 + w) = -33 (-8 * 3 + w * 3) = -33 (-24 + 3w) = -33 Solving -24 + 3w = -33 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 3w = -33 + 24 Combine like terms: -24 + 24 = 0 0 + 3w = -33 + 24 3w = -33 + 24 Combine like terms: -33 + 24 = -9 3w = -9 Divide each side by '3'. w = -3 Simplifying w = -3
| -.5=cos(pi•t/6) | | 1/x-3/4=x/1 | | 49=6u-17 | | 4l-12=8+5l | | -4t-3t=28 | | 5+0.65p=12.3 | | 3y=-2x-8 | | 3(x+5)=6x-21 | | 23+82= | | 42=-2t+9t | | 7/6multiply3/5 | | 4(w+2)=8 | | 28=-4+8x | | 6x-6y/-5z | | 6=5b+1 | | (2q+4)(3q+1)= | | 16x^4+26x^2+3=0 | | 690/a | | 1=d/4 | | X+.75x=65 | | 5cos^2x-cosx+3=0 | | -36-12x=48 | | 3-(5x+7)=17-8x | | 3(x+45)=2(x+40)+(2x) | | -6-9x+1=7x | | -2y+4x=-4 | | 4x-3(4x+21)=-143 | | -6-9+1=7x | | 4(d+50)=114 | | x^7+x^5+5=0 | | 10a-2ab= | | 8/x=-9 |